Strategies and Methods for Investigating Performance and Degradation in Solid-State Batteries Using Thiophosphate Solid Electrolytes - Hertle, Jonas; Justus Liebig University Giessen (My University, 2024)
The demand for high-performance energy storage solutions is ever-growing, driven by the increasing need for portable electronics and electric vehicles. While conventional lithiumion batteries (LIBs) are well established, they are approaching their limits in terms of energy and power density. Solid-state batteries (SSBs) offer a promising alternative with the potential for significantly higher energy densities when using lithium metal anodes. However, a major challenge remains in the reactivity of thiophosphate solid electrolytes (SEs) with cathode active materials (CAMs), leading to degradation and performance limitations. Current approaches used for the analysis of SSBs are limited. The influence of the anode in electrochemical experiments, specifically the overpotential, leads to unreliable results because these overpotentials are usually unknown and not accounted for. Degradation analysis in combination with standard cell setups using widely utilized post mortem techniques like X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry (ToF-SIMS) lack sensitivity and show overlap of different degradation pathways. To address these shortcomings, this thesis introduces two key contributions in the form of two publications: Publication I introduces a three-electrode (3E) setup for SSBs. A thin gold-plated tungsten wire is lithiated in-situ to provide a stable potential. This enables the independent measurement of cathode and anode, providing accurate information on the true rate-performance of CAMs without limitations from anode overpotential. Furthermore, single-electrode impedance analysis is rendered possible. This facilitates impedance analysis of the electrodes and removes ambiguity when fitting impedance data to equivalent circuits. Publication II introduces a reliable benchmarking method for CAM coatings. This method combines the 3E setup from publication I with ToF-SIMS analysis. A specially developed current collector is used. With the help of this current collector and ToF-SIMS analysis, a semi-quantitative analysis of the various degradation pathways is made possible. Principal component analysis (PCA) is used to cope with the large data volumes of the ToFSIMS analysis. This approach allows the complete evaluation of CAMs regarding their electrochemical performance as well as their susceptibility to degradation. By extending the knowledge of electrochemical and post mortem analysis in SSBs, this thesis paves the way for accelerated research and development. The presented concepts are transferable to other battery systems, offering broader research possibilities. Ultimately, this work contributes to the development of competitive and commercially viable SSBs.
Keywords: Festkörperbatterien; solid-state battery; solid-state batteries; solid electrolyte; reference electrode; benchmarking; cathode active material; coating; impedance spectroscopy; μ-reference electrode; μ-RE; ddc:000; ddc:540